Stability, Characterization, and Antibacterial Activity of Cinnamon (Cinnamomum burmanii) Extract Mask Preparations as Potential Skin Care Products - Lianingsih, Nestia; Yuningsih, Siti Hadiaty; Vimelia, Willen (Corespub, 2024)
This study aims to evaluate the stability, physical-chemical characteristics and antibacterial activity of a cinnamon extract (Cinnamomum burmanii) mask preparation. Cinnamon extract is obtained through the maceration method using 96% ethanol. The physical-chemical characteristics of the preparations were evaluated including water content, ash content, as well as phytochemical tests to identify active compounds such as alkaloids, flavonoids, tannins and saponins. Stability tests were carried out for 8 weeks at room temperature (25°C-30°C) and accelerated temperature (40°C), with pH and organoleptic testing parameters. Apart from that, a preference test for aroma, texture and color is also carried out using a specified rating scale. The antibacterial activity of the preparation was evaluated using the disc diffusion method against Staphylococcus aureus. The research results showed that the cinnamon extract mask preparation had good stability, physical-chemical characteristics according to standards, and promising antibacterial activity, especially at an extract concentration of 12%.